2018
DOI: 10.1039/c8nr02279h
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-terminated or reconstructed Fe3O4(001) surface: water makes a difference

Abstract: The presence of water may invert the relative stability of the bulk-terminated and reconstructed Fe3O4(001) surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 64 publications
10
53
0
1
Order By: Relevance
“…NPs of both shapes have semiconducting character, which agrees with the tunneling microscopy measurements [25,26]. The nanocube possesses very similar electronic structure to that of bulk [28] and of the (001) surface [29], with a band gap of 0.55 eV. The conductivity is dominated by electron hopping between fully coordinated Fe Oct 2+ and Fe Oct 3+ in the core of the nanocube [Fig.…”
Section: +supporting
confidence: 75%
“…NPs of both shapes have semiconducting character, which agrees with the tunneling microscopy measurements [25,26]. The nanocube possesses very similar electronic structure to that of bulk [28] and of the (001) surface [29], with a band gap of 0.55 eV. The conductivity is dominated by electron hopping between fully coordinated Fe Oct 2+ and Fe Oct 3+ in the core of the nanocube [Fig.…”
Section: +supporting
confidence: 75%
“…These observations agree well with previous results based on DFT+U and HSE calculations. 20,34 For both DBT and SCV surfaces, the distance between the first two layers is largely compressed with respect 11 to the bulk value (0.828 and 0.812 Å vs. 1.061 Å, respectively), while the distance between the second and the third layers is only slightly changed. The relaxation in the surface layers is also in accordance with that obtained by DFT+U and HSE methods.…”
Section: Resultsmentioning
confidence: 99%
“…For all the details on the DFT+U and HSE calculations on magnetite bulk and surface systems, the reader is referred to our previous studies where they are reported. 34,44 III.…”
Section: Methodsmentioning
confidence: 99%
“…properly deal with the strong correlation effects among Fe 3d electrons, 22 DFTB+U with an effective U-J value of 3.5 eV was adopted according to our previous work on magnetite bulk and (001) surface. 11,23 The convergence criterion of 10 -4 a.u. for force was used during geometry optimization, and the convergence threshold on the self-consistent charge (SCC) procedure was set to be 10 -5 a.u.…”
Section: Formentioning
confidence: 99%
“…Since SCV was discovered, two computational works have concomitantly appeared in the literature where water adsorption on such reconstructed surface was modeled by density functional theory calculations. In one of these studies by some of us, 11 adsorption of one to four water molecules on both the bulkterminated and the SCV Fe3O4 (001) surface unit cell models has been investigated by hybrid density functional calculations (HSE06). 12 We have shown that in certain experimental conditions of water partial pressure and temperature, the hydrated bulk-terminated surface may become more stable than the SCV one, that, however, is the most stable in a wide range of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%